New record of thapariella anastomusa (Trematoda: Thapariellidae) metacercariae in Northern Thailand - Waraporn Phalee (2018)
© 2018, Korean Society for Parasitology and Tropical Medicine. The family Thapariellidae has been reported in only 3 countries since 1990. The objective of this study was to identify Thapariella anastomusa metacercariae in snails in Thailand based on morphological traits using a light (LM) and a scanning electron microscope (SEM). A total of 94 Filopaludina snails were collected and identified as 50 F. martensi martensi and 44 F. doliaris. Metacercariae of T. anastomusa were recovered from the snails by the crushing method. The overall prevalence was 22.3% (21/94), and the mean intensity was 17.0 per snail. The prevalence in F. martensi martensi was 24.0% (12/50) and F. doliaris 20.5% (9/44) with the mean intensity of 18.8 and 14.8 per snail, respectively. SEM revealed traits such as a concave ventral body and well-developed oral and ventral suckers. This study represents the first report of T. anastomusa in South East Asia. While LM and SEM observations provide novel insights into T. anastomusa metacercarial morphology and life history, the trematode’s life cycle remains unclear. To date, there has been no report of T. anastomusa causing infections in humans. However, the snails F. martensi martensi and F. doliaris carrying the infective stages of T. anastomosa are frequently consumed by Thai people. This consumption, particularly uncooked snails, may present a risk of Thapariella infections in humans.